Preliminary analysis of EUSO—TA data. Issue 5 (May 2016) - Fenu, F; Piotrowski, L W; Shin, H; Jung, A; Bacholle, S; Bisconti, F; Capel, F; Eser, J; Kawasaki, Y; Kuznetsov, E; Larsson, O; Mackovjak, S; et al.
Abstract: The EUSO-TA detector is a pathfinder for the JEM-EUSO project and is currently installed in Black Rock Mesa (Utah) on the site of the Telescope Array fluorescence detectors. Aim of this experiment is to validate the observation principle of JEM-EUSO on air showers measured from ground. The experiment gets data in coincidence with the TA triggers to increase the likelihood of cosmic ray detection. In this framework the collaboration is also testing the detector response with respect to several test events from lasers and LED flashers. Moreover, another aim of the project is the validation of the stability of the data acquisition chain in real sky condition and the optimization of the trigger scheme for the rejection of background. Data analysis is ongoing to identify cosmic ray events in coincidence with the TA detector. In this contribution we will show the response of the EUSO-TA detector to all the different typologies of events and we will show some preliminary results on the trigger optimization performed on such data.